Effects of cellulose nanocrystals on the vulcanization of natural rubber/cellulose nanocrystals nanocomposite and corresponding regulating strategies. Issue 23 (8th September 2021) - Hu, Jie; Yang, Fan; Liu, Ke; Kong, Zhengqing; Qin, Jinli; Duan, Yongxin; Zhang, Jianming
Abstract: Vulcanization is a vital process in rubber processing, it endows rubber with valuable physical and mechanical properties, making rubber a widely used engineering material. In addition to vulcanization agent, reinforcing fillers play a non‐ignorable influence on the vulcanization of rubber nanocomposites. Herein, the effects of cellulose nanocrystals (CNCs) on the vulcanization of natural rubber (NR)/CNCs nanocomposite was studied. It was found that even though the addition of CNCs can effectively improve the dispersion of ZnO in NR matrix, the vulcanization of NR was inhibited. This may be attributed to the CNCs' adsorption of vulcanizing agents (DM, ZnO) and the acidic chemical environment on the surface of CNCs. In order to improve the vulcanization properties of NR/CNCs nanocomposite, tetramethyldithiochloram (TMTD) and triethanolamine (TEOA) were used as a combination accelerator and curing activator, respectively, and polyethylene glycol (PEG) was introduced to screen hydroxyl groups on the surface of CNCs to prohibit the CNCs' adsorption of vulcanizing agents. The results indicate that TMTD and TEOA effectively improved the vulcanization rate of NR/CNCs nanocomposite and increased the crosslink density by an order of magnitude. Subsequently, the tensile strength, tear strength, and so forth. of NR/CNCs nanocomposite were significantly improved. However, PEG hardly help to improve the vulcanization properties of NR/CNCs nanocomposite. In addition, the control samples without CNCs were prepared and characterized, the comparation between NR and NR/CNCs nanocomposite shows that the synergistic effect of crosslink density and CNCs' reinforcement more effectively improve mechanical properties of NR. This work not only elucidates the inhibiting mechanisms of CNCs on the vulcanization of NR, but also provides practical strategies for improving the vulcanization and properties of NR/CNCs nanocomposite. It may accelerate the application of CNCs as rubber reinforcing filler. Abstract :